2002
DOI: 10.1074/jbc.m207157200
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Adaptation to Insulin Resistance

Abstract: The ␤-cell biochemical mechanisms that account for the compensatory hyperfunction with insulin resistance (so-called ␤-cell adaptation) are unknown. We investigated glucose metabolism in isolated islets from 10 -12-week-old Zucker fatty (ZF) and Zucker lean (ZL) rats (results expressed per mg/islet of protein). ZF rats were obese, hyperlipidemic, and normoglycemic. They had a 3.8-fold increased ␤-cell mass along with 3-10-fold increases in insulin secretion to various stimuli during pancreas perfusion despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(44 citation statements)
references
References 52 publications
4
39
0
1
Order By: Relevance
“…Despite the lowered ␣-KG content in BCATm ϩ/ϩ islets stimulated with KIC, we postulate that ␣-KG generated from KIC transamination and glutamate oxidation enhances anaplerosis and TCA cycle activity to generate coupling factors of insulin secretion. Enhanced anaplerosis not only promotes mitochondrial metabolism but also increases certain mitochondrial products that may act as second messengers to amplify nutrient-stimulated insulin secretion (15,39,40). Our finding that in response to KIC stimulation, islet ATP concentration and NADPH/NADP ϩ ratio were elevated in BCATm ϩ/ϩ but not BCATm Ϫ/Ϫ islets is consistent with this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…Despite the lowered ␣-KG content in BCATm ϩ/ϩ islets stimulated with KIC, we postulate that ␣-KG generated from KIC transamination and glutamate oxidation enhances anaplerosis and TCA cycle activity to generate coupling factors of insulin secretion. Enhanced anaplerosis not only promotes mitochondrial metabolism but also increases certain mitochondrial products that may act as second messengers to amplify nutrient-stimulated insulin secretion (15,39,40). Our finding that in response to KIC stimulation, islet ATP concentration and NADPH/NADP ϩ ratio were elevated in BCATm ϩ/ϩ but not BCATm Ϫ/Ϫ islets is consistent with this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…Most interesting, these alterations occur in the absence of any significant changes in glucose oxidation indicating a compensatory adaptation that maintains overall CO 2 production. Consistent with this observation, repressed pyruvate dehydrogenase activity in rat islets exhibited no alterations in CO 2 production because of a compensatory increase in pyruvate carboxylase (52). The observation that a subunit of the mitochondrially encoded enzyme NADH dehydrogenase is inhibited by repression of a nuclear transcription factor led us to postulate that PDX1 may regulate expression of the mitochondrial transcription factor TFAM.…”
Section: Discussionsupporting
confidence: 55%
“…Sustained glucose stimulation in islet ␤-cells results in export of intermediates such as malate, citrate, isocitrate, and ␣KG from the mitochondria to the cytosol (33)(34)(35). Recent work has begun to provide evidence that this export of mitochondrial substrates is involved in the regulation of insulin secretion (3,15,20,21,32,36,37). For example, we previously demonstrated a strong correlation between PC-mediated pyruvate exchange with tricarboxylic acid cycle intermediates (pyruvate cycling) and GSIS in INS-1-derived cell lines with varying capacities for glucose response (15), and we also showed that lipid-induced impairment of GSIS results in ablation of the normal glucoseinduced rise in pyruvate cycling activity (21).…”
Section: Discussionmentioning
confidence: 99%